Searching for Gene Expression Differences in Primary Fibroblasts Between Patients with One and Two Neoplasms in Childhood. (18th January 2013) - Victor, Anja; Weis, Eva; Messow, Claudia Martina; Marron, Manuela; Haaf, Thomas; Spix, Claudia; Galetzka, Danuta
<x xml:space="preserve">Abstract</x> Genetic factors are important for developing primary and subsequent malignancies in children. This study investigated the role of genetic factors involved in DNA-repair. Designed as a feasibility study, it addressed the possibility of obtaining samples for genetic analyses from former patients through the German Childhood Cancer Registry. Testing feasibility was as important as the biological question itself. We analyzed the expression of DNA-repair genes in untreated primary fibroblasts of 20 individuals with a second neoplasm compared to 20 matched single neoplasm cases using customized cDNA microarrays (1344 gene sequences, about 800 genes). Matching was by first neoplasm, age, and year of first diagnosis. Forty-six percent of the 52 contacted second neoplasm cases and 18% of the 132 single neoplasm patients participated in the study. The DNA-repair gene results show small differences in the basal gene expression of FTH1 and CDKN1A. To our knowledge, this is the first study using gene expression arrays in untreated primary fibroblasts regarding second neoplasms after a childhood neoplasm. We were able to recruit childhood cancer patients for genetic analyses long after diagnosis. The biological importance of the differences in the DNA-repair gene expression has to be elucidated yet.